2020
DOI: 10.1002/ecs2.3096
|View full text |Cite
|
Sign up to set email alerts
|

Forest landscape structure influences the cyclic‐eruptive spatial dynamics of forest tent caterpillar outbreaks

Abstract: A fundamental question in forest insect ecology is the role of forest landscape structure, particularly the amount and spatial configuration of host tree species, in shaping the dynamics of recurring forest insect outbreaks. For forest tent caterpillar (FTC), independent studies do not converge on a singular conclusion, although all indicate that forest structure influences outbreak dynamics. These studies also vary in how they treat climate as a covariate. We evaluated the relative importance of host forest l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 48 publications
0
24
0
Order By: Relevance
“…The diversity of findings in this regard demonstrates the complexities of disentangling the spatial dynamics of trophic interactions. Recent analysis of a long outbreak time series within a single heterogeneous landscape suggested that the results of shorter-term correlational studies may be misleading [ 38 ••]. This work found that outbreak dynamics are spatially and temporally heterogeneous and characterized by travelling waves.…”
Section: Scaling-up Resistance To Landscapes and Regionsmentioning
confidence: 92%
See 1 more Smart Citation
“…The diversity of findings in this regard demonstrates the complexities of disentangling the spatial dynamics of trophic interactions. Recent analysis of a long outbreak time series within a single heterogeneous landscape suggested that the results of shorter-term correlational studies may be misleading [ 38 ••]. This work found that outbreak dynamics are spatially and temporally heterogeneous and characterized by travelling waves.…”
Section: Scaling-up Resistance To Landscapes and Regionsmentioning
confidence: 92%
“…This work found that outbreak dynamics are spatially and temporally heterogeneous and characterized by travelling waves. Portions of these waves may correlate well with some landscape attributes within a single outbreak, but the relationships are not consistent among outbreaks [ 38 ••]. These spatiotemporal outbreak patterns are influenced by host spatial structure.…”
Section: Scaling-up Resistance To Landscapes and Regionsmentioning
confidence: 99%
“…Data quality and quantity degrade as one goes back in time; Inference of causal relationships not possible. Bebi et al, 2003;Howe and Baker, 2003;DeRose and Long, 2012;Sturtevant et al, 2014;Hart et al, 2015;Meigs et al, 2015;Robert et al, 2018Robert et al, , 2020 Prospective Empirical data used to parameterize models of disturbance mechanisms to make DI inferences.…”
Section: Methodsmentioning
confidence: 99%
“…Risk of overfitting, patterns may or may not correspond with underlying process; "black-box" data mining may limit interpretation. Fleming et al, 2002;Sturtevant et al, 2014;Seidl et al, 2016b;James et al, 2017;Mezei et al, 2017;Candau et al, 2018;Itter et al, 2019;Robert et al, 2018;Brice et al, 2020;Robert et al, 2020 trees to investigate consequent fire behavior, burn intensities, and consequent effects of those intensities related to elevated fuels on vegetation composition. Such studies can support the development of more process-based models enabling the simulation of disturbance interactions based on first principles (Figures 3, 5).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation